The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ajp.23384
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genetic diversity and divergence dating of Angolan colobus monkeys (Colobus angolensis) in the eastern forests of Kenya and Tanzania: Implications for subspeciation and reconstructing historical biogeography

Abstract: Whether the Colobus angolensis that reside in the fragmented forests in eastern Kenya and Tanzania represent one subspecies or two has been debated for 50 years.Morphological and more recent genetic and ecological studies suggest that these populations represent two subspecies, C. a. palliatus and C. a. sharpei. However, their distribution of mitochondrial variation remains unresolved since the genetic study only characterized four populations at the range ends. Therefore, we characterized five populations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 78 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…The haplotype phylogeny indicated that the PT1 haplotype ( n = 1, from founder 11) is most closely related to the Rufiji River haplotype (R2), and the PT2 haplotype ( n = 2, from founder 9) is most closely related to a Shimoni, Kenya haplotype (S2) (Figure 3). These two new haplotypes differed from their most similar haplotypes in either cytochrome b or D‐loop, or both: 0% to 0.2% (cytochrome b ) and 0.4%–1.5% (D‐loop) (McDonald et al, 2022).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The haplotype phylogeny indicated that the PT1 haplotype ( n = 1, from founder 11) is most closely related to the Rufiji River haplotype (R2), and the PT2 haplotype ( n = 2, from founder 9) is most closely related to a Shimoni, Kenya haplotype (S2) (Figure 3). These two new haplotypes differed from their most similar haplotypes in either cytochrome b or D‐loop, or both: 0% to 0.2% (cytochrome b ) and 0.4%–1.5% (D‐loop) (McDonald et al, 2022).…”
Section: Resultsmentioning
confidence: 98%
“…Our analysis also included 26 haplotypes identified from nine wild Vulnerable by the 2020 IUCN Red List Assessment (Cunneyworth et al, 2020;Rovero et al, 2020) (Figure 1 and Supporting Information: Table 3). Using MEGA 10.1.7 (Kumar et al, 2018) and (Huelsenbeck & Ronquist, 2001) in Geneious 7.1 (https://www.geneious.com) and maximum likelihood (ML) analyses using PAUP 4.0 (Swofford, 2003) to characterize the phylogenetic relationships among the combined zoo and wild data set and to identify the likely geographic origins of the founding zoo population (McDonald et al, 2022). Finally, we assigned the zoo haplotypes to their founder and founder event using the AZA Angolan colobus studbook (Fogarty, 2018) and compared the founder and haplotype representation of the managed zoo population using the 2018 AZA Breeding and Transfer Plan (Gibson et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A fine-scale analysis of mtDNA enabled the precise localization of the boundary between northern and southern mitochondrial clades within the distribution of yellow baboons in central Tanzania from the coast to the eastern shore of Lake Tanganyika along the Ugalla-Malagarsi and the Ruaha-Rufiji rivers [ 35 ]. Interestingly, the Ruaha-Rufiji rivers seem to constitute a dispersal barrier also for other taxa, e.g., dwarf galagos [ 62 ] and subspecies of Colobus angolensis [ 63 ]. The contact zone of the current distributions of phenotypically well-differentiated olive and yellow baboons is also localized in East Africa but does not correspond to the boundary between northern and southern mtDNA clades.…”
Section: The Two Main Clades Mingling: Past and Present Hybridization...mentioning
confidence: 99%